Death-associated protein kinase: A molecule with functional antagonistic duality and a potential role in inflammatory bowel disease (Review) - STEINMANN, SARA (Int J Oncol, 2015)
The cytoskeleton-associated serine/threonine kinase death-associated protein kinase (DAPK) has been described as a cancer gene chameleon with functional antagonistic duality in a cell type and context specific manner. The broad range of interaction partners and substrates link DAPK to inflammatory processes especially in the gut. Herein we summarize our knowledge on the role of DAPK in different cell types that play a role under inflammatory conditions in the gut. Besides some promising experimental data suggesting DAPK as an interesting drug target in inflammatory bowel disease there are many open questions regarding direct evidence for a role of DAPK in intestinal inflammation.